Public Disclosure and Budget Transparency : Community Satisfaction with Local Financial Managemen - Hadra Mulina; Rismawati; Erniyanti Caronge (Prodi Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas PGRI Madiun, 2026)
This study investigates the influence of Public Information Transparency and Budget Socialization on Public Satisfaction with regional financial management in North Luwu Regency. Using a quantitative explanatory design, data were collected from 100 respondents through structured questionnaires and analyzed using multiple linear regression. The results show that both transparency and budget socialization significantly affect public satisfaction, with transparency emerging as the dominant variable. The findings indicate that accessible, timely, and responsive fiscal information, supported by effective communication of budget policies, enhances community trust and satisfaction. This study contributes theoretically by integrating transparency and fiscal literacy into public sector accounting discourse, and practically by offering empirical evidence for improving fiscal communication strategies at the local government level.